OPEN DATA PLATFORMS FOR A DATA COMMONS, HOW TO SUPPORT THE LIFE OF DATA BEYOND RELEASE - Hamilton, Hannah; De Paoli, Stefano; Wilson, Anna; Singh, Greg (AoIR Selected Papers of Internet Research, 2020)
In this paper we will discuss the challenges and opportunities of infusing in open data a life beyond its original public release. Indeed, it is often unclear whether open data has a life beyond the one it was initially collected for, to the extent that some authors have even described the public reuse of government data as no more than a “myth”. We will present the results of the project Data Commons Scotland launched with the idea of creating an Internet based prototype platform for creating a trustworthy common of open data, thus facilitating a life for data beyond the one of the original producer. We will discuss the results of our empirical research for the project based on 31 qualitative interviews with a number of actors, such as data producers or citizens. Moreover, we will present the results of the co-design conducted for the design of the Data Commons Scotland platform. With the results of our analysis we will reflect on the challenges of building Internet based platforms for open data supporting the generation of a common.